World War I - FlagTower (Firm); First Electronic Publishing Limited ([Boston, Mass.] : FlagTower, 1995)
A fully interactive documentary. You can play the whole story of the war from the beginning, or select a particular narrative or time period.
Title from disc label
System requirements: Multimedia PC or compatible with a 486DX or higher microprocessor; 8 MB of memory ; 2.5 MB of available hard disk space ; dual speed CD-ROM drive ; 256-color display ; Microsoft Windows 3.1 or later; mouse ; headphones or speakers
Keywords: World War(1914-1918) -- Software; Interactive multimedia; CD-ROMs.; Computer software